KONSEP DAN STRATEGI PENDIDIKAN ORANG DEWASA - Erlina Sihombing (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
Abstract The progress of science and technology today, one that needs attention is regarding the concept of education for adults. It is not always that we talk and review on education about relatively young school students the reality on the ground, that not a few adults have to get education, both informal and nonformal education, for example in the form of skills, courses, upgrading and so on. The problem that often arises is how the tips and strategies to teach adults who are not occupying school notes. Psychologically adults as students in learning activities cannot be treated like ordinary students who are sitting in school. Adults grow as individuals and have the maturity of self-concept moving from dependence as happened in childhood toward self-direction or self-direction. Maturity of adult psychology as a person who is able to self-direct, not directed, forced and manipulated by others.  Keywords: Adult Education, Independence and Learning Strategies.